The association between reading motivation and reading achievement in Chinese students: Exploring the role of personality - Spadafora, Natalie; Brandow, Ivy; Li, Miao; Volk, Anthony (Advances in Social Sciences Research Journal, 2021)
It is documented that individualistic (Western) versus collective (Eastern) societies may have different expectations of students. For example, compared to their Western counterparts who tend to be more intrinsically motivated to learn, learning in China tends to be characterized by group-level success, being prideful and ensuring positive career outcomes. Further, it is possible that individual differences, such as personality, may be mediating the relationship between reading motivation and achievement. Therefore, the purpose of this study was to explore the associations between reading motivation, personality traits and reading grade in a sample of students from Mainland China (n = 422) between the ages of 11 and 19 (M =14.61, SD = 1.55). Using path analysis, we examined if reading motivation might be working indirectly through individual personality traits to influence reading grade in this sample. Our results highlight the role of individual differences in the relationship between reading motivation and achievement. Further, results of our study emphasize the importance of fostering Openness, particularly within Chinese students, as it could be associated with higher reading achievement. Taken together, our results suggest that educators working with Chinese students should consider individual differences when fostering reading motivation to increase reading achievement in students.